Marker-Assisted Development and Evaluation of Near-Isogenic Lines for Broad-Spectrum Powdery Mildew Resistance Gene Pm2b Introgressed into Different Genetic Backgrounds of Wheat - Xu, Hongxing; Cao, Yanwei; Xu, Yunfeng; Ma, Pengtao; Ma, Feifei; Song, Liping; Li, Lihui; An, Diaoguo (Frontiers in Plant Science, 2017)
At present, most of released wheat cultivars or breeding lines in China are susceptible to powdery mildew (caused by Blumeria graminisf. sp. tritici, Bgt), so it is urgent to rapidly transfer effective and broad-spectrum powdery mildew(Pm) resistance genes into elite cultivars/lines. Near-isogenic lines (NILs) with short target gene region are very important in molecular design breeding and map-based cloning and can be developed by combining marker-assisted selection (MAS) and conventional phenotypic identification. However, none Pm gene NILs were reported by using this method in the previous studies. A new broad-spectrum dominant resistance gene Pm2b, derived from the Chinese wheat breeding line KM2939, conferred high resistance to powdery mildew at both the seedling and adult stages. In this study, with the aid of forward ground and background selection (FS and BS) using molecular markers, the Pm2b gene was introgressed into three elite susceptible commercial cultivars Shimai 15, Shixin 828 and Kenong 199 through the back-crossing procedure. With the appropriate backcrossing generations, selected population sizes and marker number for BS, the homozygous resistant BC3F2:3 NILs of Pm2b gene in the three genetic backgrounds with the highest recipient genome composition (RGC) of about 99%, confirmed by genome simple sequence repeat (SSR) markers and 660K single nucleotide polymorphic (SNP) array, were developed and evaluated for the powdery mildew resistance and agronomic traits. The different resistances and similar or improved agronomic performance between Pm2b NILs and their corresponding recurrent parents indicated their potential value in the marker-assisted breeding of the Pm2b gene. Moreover, the development of four flanked diagnostic markers (CFD81, BWM25, BWM20 and BWM21) of Pm2b gene can effectively assist the forward background selection and accelerate the transfer and use of this resistance gene.